Inherited Pragmatism - Jeremy Dennis (JAm It!)
Scholars who turn to Ralph Ellison’s novel Invisible Man to address issues of race and black representation often employ the thinking of American pragmatists such as John Dewey. However, Dewey’s record on race and that of other classical pragmatists contribute little on the topic. As a result, some scholars have suggested that Ralph Ellison brings critical attention to the idea of race in pragmatism in ways thinkers before him do not. This study challenges this view, revealing how the philosopher Immanuel Kant fulfilled this role. It also explains why illuminating Kant’s troubling views on race and their continuity in the sociology of Robert Park warrant a reconceptualization of race as a technology of power, particularly as it is explored in the missing chapter from Ellison’s novel. Ultimately, a technological consideration of the novel helps to advance it as a refutation of the essentialization of black identity in Kantian philosophy and American history.